Effect of different modified atmosphere packaging and storage time on bioactive compounds in fresh-cut Tropic Beauty peaches (Research, Society and Development, 2021)
Modified atmosphere packaging (MAP) was evaluated for respiration rate, color, total phenolic content (TPC), antioxidant activity DPPH, flavonoids and pigments of fresh-cut Tropic Beauty peach. Modified atmospheres (21% O2 [Control], 5% CO2 [MAP1], 8% CO2 [MAP2] and 0% O2 [MAP3]) were evaluated for storing fresh-cut peaches for up to 10 days in temperatures of 5ºC. MAP significantly (p